POLITICAL REPRESENTATION OF WOMEN IN PARLIAMENT: A LITERATURE REVIEW AND FUTURE RESEARCH OPPORTUNITIES - Saputri, Rini Archda; Sukmajati, Mada; Dwi Asriani, Desintha (Universitas Padjadjaran, 2023)
Over the past twenty-five years, gender and politics scholars have engaged in extensive theoretical and empirical discussions about women’s political representation. This article provides a comprehensive literature review of these studies. This study is divided into three themes: descriptive representation of women, substantive representation of women, and the correlation between descriptive and substantive representation of women. The literature review method is carried out by exploring and compiling studies on women’s political representation from various countries, classifying them based on specific topics, and mapping out what has been explored in these studies. The results of the study show that most of the research on women’s political representation is in the realm of women’s descriptive representation, which generally discusses the factors that affect the level of women’s political representation, obstacles and challenges in women’s political representation and the strategies used by women candidates in electoral politics. Meantime, studies on women’s substantive representation still need to be explored, especially in the context of countries in Asia, especially Indonesia. Then, studies on the relationship between descriptive and substantive representations of women show two debate patterns. Some experts believe a positive correlation exists between increasing the number of women’s representation and its substantive effect. Some others find no correlation between the descriptive and substantive representations of women.